2020
DOI: 10.3390/biomedicines8090370
|View full text |Cite
|
Sign up to set email alerts
|

Brassicasterol from Edible Aquacultural Hippocampus abdominalis Exerts an Anti-Cancer Effect by Dual-Targeting AKT and AR Signaling in Prostate Cancer

Abstract: In the Compendium of Materia Medica, seahorse (Hippocampus) is considered effective for the reinforcement of kidney and men’s health. However, the role of seahorse on human health lacks scientific evidence. Therefore, we evaluated the effect of seahorse on human prostate cancer using various in vitro methods and identified bioactive compound. Seahorse lipid extract (SHL) decreased androgen receptor (AR) and prostate-specific antigen (PSA) expression in dihydrotestosterone (DHT)-induced LNCaP cells of prostate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…AKT and ERK pathways are the common pathways involving tumorigenesis and targeting these pathways are proven to be effective against several cancers [ 23 , 24 ]. In addition, previous study has shown that brassicasterol inhibited prostate cancer growth by targeting AKT pathway [ 19 ]. To investigate if brassicasterol suppressed the growth of HBV + HCC through downregulation of one or both pathways, western blot was performed.…”
Section: Resultsmentioning
confidence: 99%
“…AKT and ERK pathways are the common pathways involving tumorigenesis and targeting these pathways are proven to be effective against several cancers [ 23 , 24 ]. In addition, previous study has shown that brassicasterol inhibited prostate cancer growth by targeting AKT pathway [ 19 ]. To investigate if brassicasterol suppressed the growth of HBV + HCC through downregulation of one or both pathways, western blot was performed.…”
Section: Resultsmentioning
confidence: 99%
“…The expression of PARP was inhibited by brassicasterol treatment, during which induced cleaved caspase-3 expression was noted. Brassicasterol inhibits cell migration in LNCaP cells, as well [ 125 ]. Furthermore, it inhibited n-butyl-(4-hydroxybutyl) nitrosamine (BHBN) and SS-induced carcinogenesis.…”
Section: Health Benefits and Biomedical Applications Of Phytosterolsmentioning
confidence: 99%
“…In the present investigation, the brassicasterol, 24-methylene-cholesterol, 22dehydrocholesterol, and isofucosterol were recorded as the dominant NCSs. Brassicasterolrich lipids from edible Hippocampus abdominalis have shown cytotoxicity against LNCaP human prostate cancer cells [50]. Lipid fractions rich in 22-dehydrocholesterol, brassicasterol and other marine animal specific sterols from the Persian Gulf sponge, Axinella sinoxea, have also shown cytotoxicity against human lymphoblastic leukemia (MOLT-4), human breast adenocarcinoma (MCF-7), and human colorectal adenocarcinoma (HT-29) cells.…”
Section: Anticancer Potential Of Lipids Extracted From Shellfish Speciesmentioning
confidence: 99%